Pengembangan Media Pembelajaran Berbasis Multimedia Video Pada Siswa - Supriyaddin Supriyaddin; Andi Prayudi; Siti Mardiati (STKIP Taman Siswa Bima, 2023)
The purpose of this study is to develop multimedia video-based learning media in network service technology subjects that are valid, practical and effective in class X Multimedia 2 SMK Negeri 1 Dompu. The type of research chosen by the researcher is the ADDIE model of research and development (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques are by means of interviews, observations, validation sheets, and questionnaires. The results of the learning media assessment by media experts are said to be